The komodo conflict - Patton, Jack (Battle bugs, 2016)
"The time has come for the Battle Bugs to drive General Komodo's lizard forces off Bug Island once and for all. Using all the knowledge he has gained in his time with the Battle Bugs, Max must lead the bug army in an all-out attack. If they don't defeat the lizard army this time, Bug Island will be lost--forever"--Back cover.